2020
DOI: 10.1089/ped.2020.1143
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy of Subcutaneous C1 Inhibitor in Pediatric Patients with Hereditary Angioedema

Abstract: Background: Hereditary angioedema (HAE) due to C1 inhibitor (C1INH) deficiency is characterized by recurrent attacks of edema of the skin and mucosal tissues. Symptoms usually present during childhood (mean age at first attack, 10 years). Earlier symptom onset may predict a more severe disease course. Subcutaneous (SC) C1INH is indicated for routine prophylaxis to prevent HAE attacks in adolescents and adults. We analyzed the long-term efficacy of C1INH (SC) in subjects £17 years old treated in an open-label e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 25 publications
(57 reference statements)
0
16
0
Order By: Relevance
“… 1 , 37 In 2017, the pdC1-INH for subcutaneous use, Haegarda®, was approved by the FDA (US Food and Drug Administration) for long-term prophylaxis, at a dose of 60 U/kg every 2 weeks in adolescents. 40 A recent study showed the efficacy and safety of the medication also in children. 40 However, its use has not yet been approved in Brazil.…”
Section: Long-term Prophylaxismentioning
confidence: 99%
See 2 more Smart Citations
“… 1 , 37 In 2017, the pdC1-INH for subcutaneous use, Haegarda®, was approved by the FDA (US Food and Drug Administration) for long-term prophylaxis, at a dose of 60 U/kg every 2 weeks in adolescents. 40 A recent study showed the efficacy and safety of the medication also in children. 40 However, its use has not yet been approved in Brazil.…”
Section: Long-term Prophylaxismentioning
confidence: 99%
“… 40 A recent study showed the efficacy and safety of the medication also in children. 40 However, its use has not yet been approved in Brazil.…”
Section: Long-term Prophylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…Levy et al 55 reported an analysis of safety and efficacy data from 10 pediatric patients (mean age, 13.3 years; range, 8-16 years) who participated in the COMPACT OLE. Five were treated with C1INH(SC) 40 IU/kg SC, and 5 were treated with C1INH(SC) 60 IU/kg SC.…”
Section: Outcomes In Pediatric Patientsmentioning
confidence: 99%
“…4,8 While on rare occasions attacks may occur in the first year of life, there has been a single documented case of an HAE attack occurring in utero in a mother who had a facial attack while in active labor. 9,10 The mean age of the first HAE episode is 10 years, and approximately 40% of patients experience their first episode by age 5 years. 3,4,8 The onset of clinical symptoms at an early age is associated with a more severe disease course, including more HAE episodes per year and more hospitalizations for HAE-associated symptoms.…”
Section: Introductionmentioning
confidence: 99%